COAT OF ARMS AND FLAG OF THE MUNICIPALITY OF KOSOVO MITROVICA (Heritage, 2020)
Heraldic is the auxiliary science of history that deals with the research of coat of arms and vexillology is the science that emerged from heraldic and deals with the study of flags. The first town coats of arms in the South-Slavic area appeared in 13th century and some much later. Kosovska Mitrovica is a city in the North of Kosovo and Metohija in the Republic of Serbia and it got its first real coat of arms-emblem after World War Two. The municipal authorities announced the competition for the new coat of arms that was published in “Vecernje Novosti” in 2011. Nine works participated in the competition. The five-member panel that was supposed to chose the ideal solution suggested the municipal authorities to annul the competition since no option was appropriate for them. The municipal authority annulled the competition but they noticed the its mistake soon and corrected it very quickly after that. In that way municipality Kosovska Mitrovica got its coat of arms and a flag as well. The coat of arms of Kosovska Mitrovica municipality fully reflects its historical, cultural, religious, geographic and economic features but also the natural elements of the Kosovska Mitrovica municipality with its distinctive features. The coat of arms exists in three forms: small, medium and large depending of municipality’s need and in accordance with the unwritten heraldic practice regarding the use of coat of arms of cities and municipalities in the Republic of Serbia. The municipal flag is represented on the large coat of arms of the municipality but it is also used as a separate symbol of the municipality.
Keywords: Kosovska Mitrovica, heraldry, coat of arms, coats of arms, vexicology, flag, flags.